Identifying Primates and Examining Nest Characteristics of Orang Utan in Sungai Rawog Conservation Area - Nor Aifat A.Rahman; Rames, Y.; Indavid, A. W; Jambre, A.; Firman, N. A. (Sabah Forestry Department, 2024)
The decline in the population of primates is a serious concern and is primarily attributed to various anthropogenic factors. This study focuses on the primate diversity and nest characteristics of Orangutan within the Sungai Rawog Conservation Area (SRCA). Its goals are to identify primate species and categorize orangutan nests in SRCA. This study was conducted for five days by using a non-invasive sampling method which are by employed direct observation along main roads and cruising the river. Data collected included primate species and orangutan nest counts. For nest characteristics, the location and successional stages of orangutan nests were determined to study their features. As a result, three species of primates were identified which are Long-Tailed Macaque (Macaca fascicularis), Eastern Grey gibbon (Hylobates funereus) and Borneon Orangutan (Pongo pygmaeus). Forty-five orangutan nests were counted along the main roads and trails. Trail 1 to trail 5 consist of the highest number of Orangutan nest count compared to other trails. From the observation, most of the Orangutan’s nest were built at the edge of the branch tree and the most common successional stage is at the stage in which the structure of the nest has completely ruptured and only left with few branches and twigs. While the least observed successional stage was at the stage in which the nests are quite old and the leaves used in building the nests were brown in colour. The findings imply that the movement of primates is affected by the availability of food and the size of their home ranges. Primates observed less frequently in certain regions are closely tied to their established home ranges and their patterns of movement. The lack of sufficient food resources in these areas serves as a significant factor contributing to the reduced sightings of primates. The method by which an orangutan constructs its nest can vary based on several factors, such as individual preferences, environmental characteristics, and ecological conditions. This information will help to provide baseline data to enhance conservation efforts.